(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper carries out an analytical mapping of the scientific production of researchers participating in the Advertising and Propaganda Group, with data relating to 31 years of intellectual contribution by this research group at the Intercom National Congress. The corpus collected for analysis relates to the papers available in the PORTCOM collection (1994-2000) and in the electronic annals of the Intercom Portal (2001-2024). It adopts the bibliometric historiography method, carrying out procedures for retrieving scientific production, bibliometric data processing and historiographic analysis. VantagePoint text and data mining software was used to process the metadata. The database’s indexing period (1994 to 2024) identified 1,407 productions, authored by 1,150 researchers. The results of the research point to: the maintenance of the theoretical framework in canonical foreign authors; the low diversity among Brazilian researchers; the high concentration of scientific production in the country; public universities as the most productive institutions.